(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The goal of this research is to establish procedures for auditing deposit insurance activity to reduce the risks of financial failure for the research sample and to predict the financial failure of the company using the Altman model. The research sample is the Iraqi Deposit Insurance Company for the fiscal year 2021. The researchers also reached a set of conclusions, most notably that the company operates in a high-risk environment, and this was supported by the Altman Index, which showed a low result. The study also revealed many risks (financial, operational, business, external) that contribute to financial failure in deposit insurance activities. Accordingly, the researchers proposed several recommendations, the most important of which are for management to take into account the risks in the environment in which the company operates and work to reduce those risks and the need for the auditor to rely on audit procedures that contribute to reducing the risks of financial failure to guarantee deposits.